2020
DOI: 10.1073/pnas.2008245117
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes guided by mesenchymal stem cells on a 3D microgel platform enhance angiogenesis in vivo at a low-cell dose

Abstract: Therapeutic factors secreted by mesenchymal stem cells (MSCs) promote angiogenesis in vivo. However, delivery of MSCs in the absence of a cytoprotective environment offers limited efficacy due to low cell retention, poor graft survival, and the nonmaintenance of a physiologically relevant dose of growth factors at the injury site. The delivery of stem cells on an extracellular matrix (ECM)-based platform alters cell behavior, including migration, proliferation, and paracrine activity, which are essential for a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
5
37
0
Order By: Relevance
“…In a biological context, 2D platform offers the least resistance at a single-cell level wherein cellular turnover, metabolism, and protein synthesis occur in an accelerated manner. In contrast, in a 3D tissue-like architecture these processes occur in concert with changes in the local extracellular environment, receiving feedback responses from a multitude of cells that are tightly packed in a small volume ( Baker and Chen, 2012 ; Thomas et al, 2018 ; Thomas et al, 2020 ). With the recent advancements in bioengineering tools, 3D culture systems with varying degrees of complexities have gained significant traction in the field of drug testing and drug discovery ( Figure 2 ).…”
Section: Building Physiologically Relevant In Vitromentioning
confidence: 99%
“…In a biological context, 2D platform offers the least resistance at a single-cell level wherein cellular turnover, metabolism, and protein synthesis occur in an accelerated manner. In contrast, in a 3D tissue-like architecture these processes occur in concert with changes in the local extracellular environment, receiving feedback responses from a multitude of cells that are tightly packed in a small volume ( Baker and Chen, 2012 ; Thomas et al, 2018 ; Thomas et al, 2020 ). With the recent advancements in bioengineering tools, 3D culture systems with varying degrees of complexities have gained significant traction in the field of drug testing and drug discovery ( Figure 2 ).…”
Section: Building Physiologically Relevant In Vitromentioning
confidence: 99%
“…[ 86 ] Our laboratory has fabricated a tunable type‐I collagen microgel platform that was able to modulate the paracrine angiogenic action of human mesenchymal stem cells (hMSCs). [ 97 ] The microgels were prepared by crosslinking with 4‐armPEG and optimized by varying polymer concentration, collagen‐crosslinking ratio as well as embedding cell densities. Cells embedded into the microgel were able to induced angiogenesis, ambulation improvement, reduce inflammation and necrosis in a mice model of CLTI.…”
Section: Biomaterials Application For Cltimentioning
confidence: 99%
“…Cells embedded into the microgel were able to induced angiogenesis, ambulation improvement, reduce inflammation and necrosis in a mice model of CLTI. [ 97,98 ] A more in‐depth molecular analysis to understand the influence of macromolecular concentration on the paracrine phenotype of hMSCs revealed that the interaction of collagen I with hMSCs’ integrins was crucial in the secretion of pro‐angiogenic mediators. Moreover, collagen microgels significantly improved the performance of similar cell‐delivery platforms with a 20‐fold lower cell dose, as well as allowed to elucidate a mechanism involving pathways modulated in vivo.…”
Section: Biomaterials Application For Cltimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies pointed out the beneficial effects of MSC in different disease models, mainly due to the paracrine secretion of pro-angiogenic, anti-apoptotic and anti-inflammatory trophic factors that can contribute to tissue repair [ 20 , 21 , 22 , 23 , 24 , 25 ]. The regenerative potential of MSC is so promising that several groups are already developing delivery methods of MSC on a 3D cell-delivery platform, which can be an alternative to improve cryoprotection, graft survival, angiogenic activity and prolonged cell function in vivo in order to explore the full potential of MSC in regenerative medicine [ 26 ].…”
Section: Introductionmentioning
confidence: 99%